2014
DOI: 10.1016/j.jmb.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAc Modification of tau Directly Inhibits Its Aggregation without Perturbing the Conformational Properties of tau Monomers

Abstract: The aggregation of the microtubule-associated protein tau into paired helical filaments to form neurofibrillary tangles constitutes one of the pathological hallmarks of Alzheimer's disease. Tau is post-translationally modified by the addition of N-acetyl-D-glucosamine O-linked to several serine and threonine residues (O-GlcNAc). Previously, increased O-GlcNAcylation of tau has been shown to block the accumulation of tau aggregates within a tauopathy mouse model. Here we show that O-GlcNAc modification of full-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 69 publications
2
98
0
Order By: Relevance
“…Studies in bigenic MAPT/APP mutant mice showed that inhibition of OGA prevented cognitive decline and amyloid plaque formation [51] and in JNPL3, tauopathy mice acted to block the formation of hyperphosphorylated tau, the development of tau aggregates, and neurodegeneration [52]. Various protective mechanisms are possible; however, it is interesting to note that O-GlcNAcylation of tau was recently shown to attenuate tau aggregation in vitro [53]. Inhibiting acetylation of tau has also been proposed as a therapeutic strategy.…”
Section: Therapeuticsmentioning
confidence: 99%
“…Studies in bigenic MAPT/APP mutant mice showed that inhibition of OGA prevented cognitive decline and amyloid plaque formation [51] and in JNPL3, tauopathy mice acted to block the formation of hyperphosphorylated tau, the development of tau aggregates, and neurodegeneration [52]. Various protective mechanisms are possible; however, it is interesting to note that O-GlcNAcylation of tau was recently shown to attenuate tau aggregation in vitro [53]. Inhibiting acetylation of tau has also been proposed as a therapeutic strategy.…”
Section: Therapeuticsmentioning
confidence: 99%
“…Surprisingly, however, sustained OGA inhibition over a period of months did not lead to a reduction in phosphorylation of soluble tau (78), causing the authors to speculate that O-GlcNAc may itself hinder tau aggregation independent of phosphorylation. Analysis of various aggregation-prone tau fragments (78) and, more recently, full-length tau (84) showed that O-GlcNAc at Ser-400 hinders aggregation of tau in vitro without affecting the conformation of tau.…”
Section: Effects Of Pharmacological Inhibition Of Oga On Tau Toxicitymentioning
confidence: 99%
“…Similarly, O-GlcNAc modification may increase ensemble dynamics and thereby suppress precipitation of aggregation-prone proteins. Interestingly, pharmacological intervention that increases O-GlcNAc is reported to inhibit tau protein aggregation in vitro [47] and to prevent amyloid plaque formation in a mouse model of Alzheimer's disease [48]. O-GlcNAc emerged in metazoans and O-GlcNAc-modified Nup98 gel lacks the amyloid-like b structures found in the rigid regions of the S. cerevisiae Nups that are required for hydrogel formation.…”
Section: Nuclear Poresmentioning
confidence: 99%